Effect of Inorganic and Organic Liquid Fertilizer Application with Different Application Frequency on Growth of Yielding Tea - Athallah, Faris Nur Fauzi; Wulansari, Restu; Pranoto, Eko; Alimin, Muhammad (Jurnal Agro Industri Perkebunan, 2021)
Input factor is one of the determinator the quality and response of the tea plant growth. Inorganic fertilizer input still dominates in Indonesian plantations due to the lack of comprehensive evaluation of organic fertilizers, especially in liquid form. This study aims to determine the effect of inorganic and organic liquid fertilizer applications and the frequency of their application on the growth of tea plants. The experiment was carried out based on a Randomized Block Design (RBD) consisting of six treatment combinations, including tap water application once a week, tap water once every two weeks, 1% urea once a week, 1% urea every two weeks, 1% POC once a week and 1% POC once every two weeks. Experiments were carried out on yielding tea plants with the 3rd year of pruning stage. The parameters observed were shoot production (kg.plot-1), weight of banji and pekoe (g.100g-1) and the ratio of banji/pekoe. The results showed that the application of urea foliar fertilizer and liquid organic fertilizer with different application frequencies did not have a significant effect on each observed parameter. Application of 1% liquid organic fertilizer once every two weeks has the potential to increase tea productivity by showing a relatively high production of tea (6.88 kg.plot-1) compared to other treatments.